Exploring the Implementation of Project-Based Learning (PBL) in Teaching Recount Text Writing in Secondary School - Hady, Naila Azfa; Pujiawati, Nia; Wahyuna, Yuna Tresna (FKIP - Universitas Riau, 2025)
English writing, especially recount text writing, is a challenging skill for secondary school students in Indonesia due to difficulties in organizing ideas, grammar, and motivation. Project-based learning (PBL) is a student-centered approach that encourages active engagement through meaningful, collaborative projects. This qualitative case study investigated how PBL was implemented in teaching recount text writing and the challenges faced by the teacher. Data were collected through classroom observations and semi-structured interviews with an English teacher applying Stoller’s ten-step PBL framework. The findings showed that the teacher successfully implemented most PBL stages, including theme selection, project structuring, information gathering, drafting, revising, presenting, and evaluation. Adaptations were made to address students’ limited grammar skills, vocabulary, and resource constraints. Challenges included students’ difficulties with self-assessment and inconsistent motivation. The study highlights the importance of balancing student autonomy with structured linguistic support and flexible resource use. These findings provide practical insights for teachers and curriculum developers aiming to improve writing instruction and student engagement in resource-limited EFL classrooms.